Aspirin vs. Low-Molecular-Weight Heparin in Orthopedic Trauma: A Systematic Review and Meta-Analysis - Mohammed Alenezi; Abdulrahman O. Al-Naseem; Abdulrahman Alenezi; Yahya Ali; Abdullah Almehandi; Anthony Albers; Owayed Al Mutairi; Ali Jarragh (Journal of Clinical Medicine, 2026)
Introduction: Venous thromboembolism (VTE) remains a major complication following orthopedic trauma and fracture surgery. Low-molecular-weight heparin (LMWH) is widely used for prophylaxis; however, aspirin (ASA) has emerged as a potential alternative due to its ease of administration and cost-effectiveness. This study aimed to compare the efficacy and safety of aspirin (ASA) versus low-molecular-weight heparin (LMWH) in orthopedic trauma patients. Methods: A systematic review and meta-analysis was conducted by searching PubMed, Cochrane Library, and Google Scholar. Randomized controlled trials and comparative observational studies evaluating aspirin (ASA) versus low-molecular-weight heparin (LMWH) for venous thromboembolism (VTE) prophylaxis in orthopedic trauma patients were included. Outcomes assessed included overall venous thromboembolism (VTE), deep-vein thrombosis (DVT), pulmonary embolism (PE), fatal PE, mortality, bleeding complications, wound site infection, and hematoma formation. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using a random-effects model. Heterogeneity was assessed using the I(2) statistic. Results: Five studies comprising a heterogeneous orthopedic trauma population were included. No statistically significant difference between aspirin (ASA) and low-molecular-weight heparin (LMWH) in the incidence of venous thromboembolism (VTE) was noted (OR 0.52, 95% CI 0.02–12.25, p = 0.68). No significant differences were observed in the incidence of DVT between aspirin (ASA) and low-molecular-weight heparin (LMWH) (OR 1.00, 95% CI 0.46–2.16, p = 1.00). Pulmonary embolism (PE) (OR 0.96, 95% CI 0.72–1.28, p = 0.80), fatal PE (OR 0.55, 95% CI 0.18–1.65, p = 0.28), and mortality (OR 1.02, 95% CI 0.68–1.54, p = 0.91) were comparable between the two groups. Similarly, no significant differences were observed in bleeding complications (OR 0.95, 95% CI 0.86–1.05, p = 0.33) or wound complications (OR 1.05, 95% CI 0.81–1.37, p = 0.70). Hematoma formation showed a trend favoring aspirin (ASA) (OR 0.36, 95% CI 0.13–1.02, p = 0.05), although this did not reach statistical significance. Conclusions: Aspirin (ASA) may be a reasonable alternative to low-molecular-weight heparin (LMWH) for venous thromboembolism (VTE) prophylaxis in selected orthopedic trauma patients, with comparable outcomes for pulmonary embolism (PE), mortality, bleeding and wound complications. Larger high-quality randomized trials with standardized protocols in clearly defined orthopedic trauma populations are warranted to confirm these findings and guide clinical decision-making.